The Use of Zep Quiz as a Digital Quiz-Based Learning Tool in Teaching Basic Chemical Laws on Student Learning Motivation - Nurfajriah, Mufliha; Rahman, Nurul Athiah; Meylani, Karina; Kaffila, Aufa Rahmani; Bahriah, Evi Sapinatul (Universitas Nusa Cendana, 2026)
The purpose of this study was to determine the relationship between the use of digital learning media Zep Quiz on student learning motivation in the material of Basic Chemical Laws at SMA Ciputat. This study used a quantitative descriptive method. The research sample was 71 grade X students determined by purposive sampling. The instrument used was a questionnaire consisting of 25 question items with two main aspects, namely internal and external motivation using a four-point Likert scale (strongly disagree, disagree, agree, strongly agree). The data obtained by calculating the average percentage and explained descriptively. The results showed that student learning motivation was in the high category, with an average score of 82.65. This indicates that the use of Zep Quiz is related to high student learning motivation.